Conserved pattern of tangential neuronal migration during forebrain development. - Métin, C; Alvarez, C; Moudoux, D; Vitalis, T; Pieau, C; Molnár, Z (2007)
Origin, timing and direction of neuronal migration during brain development determine the distinct organization of adult structures. Changes in these processes might have driven the evolution of the forebrain in vertebrates. GABAergic neurons originate from the ganglionic eminence in mammals and migrate tangentially to the cortex. We are interested in differences and similarities in tangential migration patterns across corresponding telencephalic territories in mammals and reptiles. Using morphological criteria and expression patterns of Darpp-32, Tbr1, Nkx2.1 and Pax6 genes, we show in slice cultures of turtle embryos that early cohorts of tangentially migrating cells are released from the medial ganglionic eminence between stages 14 and 18. Additional populations migrate tangentially from the dorsal subpallium. Large cohorts of tangentially migrating neurons originate ventral to the dorsal ventricular ridge at stage 14 and from the lateral ganglionic eminence from stage 15. Release of GABAergic cells from these regions was investigated further in explant cultures. Tangential migration in turtle proceeds in a fashion similar to mammals. In chimeric slice culture and in ovo graft experiments, the tangentially migrating cells behaved according to the host environment - turtle cells responded to the available cues in mouse slices and mouse cells assumed characteristic migratory routes in turtle brains, indicating highly conserved embryonic signals between these distant species. Our study contributes to the evaluation of theories on the origin of the dorsal cortex and indicates that tangential migration is universal in mammals and sauropsids.